An Analysis of the Relevance between the State Islamic Religious Higher Education Institutions (Perguruan Tinggi Keagamaan Islam Negeri) and the Ministry of Religious Affairs Strategic Plans in Developing Higher Education Quality - Makbulloh, Deden; Yulianti, Iin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
The strategic plan of the Ministry of Religious Affairs of the Republic of Indonesia must be elaborated hierarchically into the strategic plans of Islamic Religious Higher Education Institutions based on their respective potential. The strategic plan's implementation determines the achievement and quality of higher education. Therefore, strategic plans must be developed in compliance with standards and guidelines that can direct policies regarding educational quality. This study aims to compare the relevance of Islamic Religious Higher Education Institutions' strategic plans to the Ministry of Religious Affairs of the Republic of Indonesia's strategic plans for developing religious higher education quality. The descriptive analytical method was used in the research to understand the actual reality.Furthermore, researchers conducted extensive research to assess the strategic plan for higher education development. The data sources for this study were gathered by employing the snowball technique. The researcher gathered the data through documentation and online interviews. The principle of Verstehen was used to conduct data analysis concurrently with data collection. The findings revealed that the content, structure, and systematics of the State Islamic Religious Higher Education Institutions' strategic plans differ. This difference is due to university autonomy and the low relevance of the strategic plans of State Islamic Religious Higher Education Institutions and the Ministry of Religious Affairs. At the time of this research, no main reference was used in preparing the strategic plan of the State Islamic Religious Higher Education Institutions that referred to the strategic plan of the Ministry of Religious Affairs of the Republic of Indonesia.